Beidou-3 System-enabled Multi-Satellite Comprehensive Calculation Timing Method Based on Analytic Hierarchy Process. Issue 1 (1st December 2022) - Zhao, Ruifeng; Lu, Jiangang; Li, Haobin; Zeng, Kaiwen; Zheng, Wenjie
Abstract: The large-scale access to distributed energy and massive devices puts forward higher requirements for the timing precision of power systems. With the completion of networking of the Beidou-3 (BD3) satellite system, using the BD3 system as a clock source will gradually become mainstream. The shift of timing signals from GPS to BD3 will improve national security and be of great value for improving timing precision and developing advanced application functions. In this paper, aiming at the problems such as the decrease of timing precision caused by interference in the timing signal transmission process, the BD3 system-enabled multi-satellite timing architecture is constructed, and the satellite timing precision evaluation indicator system based on the analytic hierarchy process is proposed. The multi-satellite comprehensive calculation timing method is put forward to solve the problem of low timing precision of single-satellite timing.